PERLINDUNGAN HUKUM TERHADAP PEKERJA ANAK DALAM PERSFEKTIF UNDANG-UNDANG KETENAGAKERJAAN - Nurhotia Harahap (Yurisprudentia: Jurnal Hukum Ekonomi, 2021)
Discussing about children is a discussion that is always hotly discussed and has never been discussed throughout the history of life. Because children are the nation's generation and will be the successors of development, it means that the generation that has been prepared as a subject is like the implementation of a sustainable building and who will be the holder of control in the future of the State. Therefore, child protection is very meaningful so that the potential of resources and builds real human character towards a just and prosperous society. Related to the discussion about children, it is part of an investment that makes it an indicator of the success of a nation when working on its development in the future. The success of child development will certainly determine the potential of human resources in the future, so that it is the generation that will become the nation's successor so that they must be better prepared and directed from an early age so that they can grow and develop into children who are physically and mentally healthy, advanced, independent. and prosperous, become quality resources and can face challenges in the future.